Taxonomic review of the genus Ammophilomima (Diptera: Asilidae: Leptogastrinae) in Japan - Kuroda, Keita; Ohishi, Hisashi (Zootaxa, 2019)
The genus Ammophilomima from Japan is reviewed. No species of this genus have been known from Japan, although a species that is now assigned the name Lobus trimucronatus (Hermann, 1917) was once treated as an Ammophilomima species. In the present study, two new Ammophilomima species are recorded for Japan; i. e. A. amamiensis sp. nov. from Amamioshima Is. and Tokunoshima Is. and A. rikioi sp. nov. from Okinawa Is. Morphological characteristics that distinguish these two Japanese species from other Ammophilomima species and those that separate the Japanese species are presented.